The growth effects of tax rates in the OECD - Gemmell, Norman; Kneller, Richard; Sanz, Ismael (Wiley, 2014)
This paper explores the merits of macro- and micro-based tax rate measures within an open economy ‘fiscal policy and growth’ model. Using annual data for 15 OECD countries we find statistically small, non-robust long-run growth effects of macro-based average tax rates on capital income and consumption, but some evidence for average labor income tax effects. Changes in ‘micro’ marginal income tax rates at both the personal and corporate levels yield statistically robust GDP responses of modest size. Both domestic and foreign corporate taxes appear relevant. In general, tax effects on GDP operate largely via factor productivity rather than factor accumulation.